Limitações e potencialidades do Programa de monitoramento da biodiversidade e do uso de recursos naturais - ProBUC - para a gestão ambiental de unidades de conservação do Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
The monitoring program of biodiversity and sustainable use of natural resources Amazonian PAs - ProBUC - fits within a global context of the need to assess the management of protected areas. Its importance lies in being a form of participatory monitoring community based on the protection of biodiversity and sustainable use of resources naturas. This alternative arises from the difficulties to carry out conventional monitoring, especially in tropical countries such as Brazil. In parallel, this program becomes relevant also for being innovative in the context of Amazonian conservation units. Thus, the ProBUC intended to assist the management of Amazonian state UCs by providing data that will guide investments and policies that promote local development associated biodiversity conservation. This research is intended to evaluate it identified limits and potential. Consults on qualitative analysis of interviews of three actors involved in its implementation and operation - managers, specialists and community - as well as on the literature review of international experiences on participatory monitoring. Moreover, visits to protected areas where this monitoring program is executed, the RDS Uatumã and Uacari PAREST and the Rio Negro Norte Sector, as well as attendance at meetings evaluative allowed direct observation to obtain relevant information for making this dissertation. It was found that the ProBUC has not influenced the management of PAs as intended. In general, in communities, is seen only as a program that aims to strengthen the local environmental protection without presenting concrete results. There is a discourse of widespread recognition of its importance that belies the ignorance of their goals. This program needs to be valued by Amazonas state government and, thus, to consolidate the three PAs is implemented instead of being expanded upon. All respondents confirmed their contribution to the expansion of environmental awareness community where it operates. The program activities are still restricted to the collection of information through their monitors. However, the RDS surveyed remains a great expectation about their results. There is an urgent need for better coordination between the CEUC, program management agency, and governmental and non-governmental partner organizations that can contribute to better management of ProBUC. On the other hand, the major involvement of communities requires consideration of their needs and interests mediated by sustainable use of resources and species. After all, policies of the management plan and income generation are fundamental in this sense, because the socio-economic benefits are important to stimulate their role.
Keywords: Monitoramento participativo; ProBUC; Biodiversidade; Desenvolvimento local; Community monitoring; Biodiversity; Local development; CIÊNCIAS AGRÁRIAS